Imaging in Parkinson disease surgery. - Basto, Margarida A (2003)
Parkinson's disease is a progressive degenerative disease of the central nervous system frequently becoming motor disabling. Deep brain stimulation is one more therapeutic option. The authors describe the different steps of this therapeutic procedure with detail on imaging protocol to the precise and exact targeting of subthalamic nucleus. MR and CT imaging on stereotactic conditions are the imaging support to the determination of the anatomic target allowing also the choose of trajectory for the surgical procedure. Neurophysiologic exploration and clinical evaluation during the surgery give us the functional target. Deep brain stimulation has been revealing as a safe and effective therapy on some cases of Parkinson's disease with a significant improvement on quality of life of those patients. The brain imaging is a fundamental tool on target determination.